A Systematic Review of Obesity and Binge Eating Associated Impairment of the Cognitive Inhibition System - Saruco, Elodie; Pleger, Burkhard (Frontiers in Nutrition, 2021)
Altered functioning of the inhibition system and resulting higher impulsivity are known to play a major role in overeating. Considering the great impact of disinhibited eating behavior on obesity onset and maintenance, this systematic review of the literature aims at identifying to what extend the brain inhibitory networks are impaired in individuals with obesity. It also aims at examining whether the presence of binge eating disorder leads to similar although steeper neural deterioration. We identified 12 studies that specifically assessed impulsivity during neuroimaging. We found significant alteration of neural circuits primarily involving frontal and limbic regions. Functional activity results show BMI-dependent hypoactivity of frontal regions during cognitive inhibition, and either increased or decreased patterns of activity in several other brain regions, according to their respective role in inhibition processes. The presence of binge eating disorder results in further aggravation of those neural alterations. Connectivity results mainly report strengthened connectivity patterns across frontal, parietal, and limbic networks. Neuroimaging studies suggest significant impairment of various neural circuits involved in inhibition processes in individuals with obesity. The elaboration of accurate therapeutic neurocognitive interventions however requires further investigations, for a deeper identification and understanding of obesity related alterations of the inhibition brain system.